The Maillard reaction end product Nε-carboxymethyllysine is metabolized in humans and the urinary levels of the microbial metabolites are associated with individual diet. Issue 4 (2nd February 2023) - Tagliamonte, Silvia; Troise, Antonio Dario; Ferracane, Rosalia; Vitaglione, Paola
Abstract : Gut microbial metabolites of dietary Maillard reaction end product N ε -carboxymethyllysine are excreted in urine from healthy subjects and the concentrations are associated with some aspects of the individual habitual diet. Abstract : During food processing most of the thermally-driven chemical reactions start off on the side chain amino group of lysine generating structurally modified compounds with specific metabolic routes. Upon human digestion, dietary N ε -carboxymethyllysine (CML) may enter the colon and undergo gut microbial metabolism. However, little is known about the in vivo metabolic fate of dietary CML and its relationship with the habitual diet. We explored by hydrophilic interaction liquid chromatography tandem mass spectrometry the metabolites of CML in urine samples collected from 46 healthy subjects and studied the associations with diet. Mean concentration of N -carboxymethylcadaverine (CM-CAD), N -carboxymethylaminopentanoic acid (CM-APA), N -carboxymethylaminopentanol (CM-APO), and the N -carboxymethyl-Δ1-piperideinium ion were 0.49 nmol mg −1 creatinine, 1.45 nmol mg −1 creatinine, 4.43 nmol mg −1 creatinine and 4.79 nmol mg −1 creatinine, respectively. The urinary concentration of CML, its metabolites and lysine were positively correlated. Dietary intake of meat products negatively correlated with urinary excretion of CML and CM-APA; conversely dietary plant-to-animal proteins ratio positively correlated with urinary CML and its metabolites. The identification and quantification of CML metabolites in urine and the associations with diet corroborate the hypothesis that CML, an advanced glycation end-product, can undergo further biochemical transformations in vivo . The gut microbiome may have a major role in human metabolism of dietary CML.